UK Prospective Diabetes Study. XII: Differences between Asian, Afro-Caribbean and white Caucasian type 2 diabetic patients at diagnosis of diabetes. UK Prospective Diabetes Study Group. - Meyer, L; Manley, S; Frighi, V; Burden, F; Neil, H; Holman, R; Turner, R (1994)
Clinical and biochemical variables and prevalence of complications at diagnosis of diabetes were assessed in 5098 Type 2 diabetic patients in the UK Prospective Diabetes Study of whom 82% were white Caucasian, 10% Asian of Indian origin, and 8% Afro-Caribbean. The Asian patients were (p < 0.001) younger (mean age 52.3, 47.0, 51.0 years), less obese (BMI 29.3, 26.7, 27.9 kg m-2), had a greater waist-hip ratio, lower blood pressure (systolic 145, 139, 144, diastolic 87, 86, 89 mmHg) and prevalence of hypertension. They were more often sedentary (19, 39, 15%), more often abstained from alcohol (21, 55, 25%) and had a greater prevalence of first degree relatives with known diabetes (36, 44, 34%). The Afro-Caribbean patients had (p < 0.001) higher fasting plasma glucose (11.9, 11.3, 12.5 mmol l-1), more severely impaired beta-cell function (45, 35, 28% normal) and less impaired insulin sensitivity (23, 19, 27% normal) by homeostasis model assessment, lower triglyceride (1.8, 1.8, 1.3 mmol l-1), and higher HDL-cholesterol (1.05, 1.03, 1.17 mmol l-1). Prevalence of a history of myocardial infarction, stroke or intermittent claudication at diagnosis was similar. The prevalence of ischaemic ECG (Minnesota code), microalbuminuria (urine albumin > 50 mg l-1), retinopathy ('191' grading of retinal photographs), and neuropathy (abnormal vibration perception threshold or absent leg reflexes) was also similar. At diagnosis of Type 2 diabetes there were no differences in prevalence of complications between white Caucasian, Asian, and Afro-Caribbean patients although differences were found in other clinical and biochemical variables.